Analysis of the Role Indonesian Sharia Bank in Developing Halal Tourism in Makassar City - K, Amiruddin; Ismawati,; Ahmad Tamami, (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2024)
This research aims to look at the role of Bank Syariah Indonesia in developing halal tourism in Makassar City. This research uses primary and secondary data by conducting interviews, literature studies, and documentation. This research uses qualitative research methods and a descriptive approach. The research results show that Bank Syariah Indonesia in Makassar City has a role in developing halal tourism in the culinary business sector, as well as travel service providers and lodging providers, through financing provided to halal tourism business actors. The financing provided by Bank Syariah Indonesia in Makassar City to business actors is micro-business financing and Rahn financing, which uses Murabahah and Rahn contracts.